2013
DOI: 10.1002/lary.23316
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical course of facial nerve paresis following cochlear implant surgery

Abstract: Objectives/Hypothesis:To describe the prevalence, clinical course, and outcomes of facial nerve paresis following cochlear implantation and to identify variables associated with poor definitive facial nerve function.Study Design:Retrospective cohort study with systematic literature review.Methods:All patients who underwent cochlear implantation between January 1990 and December 2010 at a single tertiary academic referral center were reviewed. Data including clinical presentation, intraoperative findings, onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 40 publications
(130 reference statements)
1
47
0
2
Order By: Relevance
“…a b c Fig. 1 12,16,17]. Most of the studies reported 0.7 % incidence of FN palsy after CI [9,11,18], which is in the range of the present study ( Table 2).…”
Section: Results Divided According To Time Of Onsetsupporting
confidence: 55%
See 3 more Smart Citations
“…a b c Fig. 1 12,16,17]. Most of the studies reported 0.7 % incidence of FN palsy after CI [9,11,18], which is in the range of the present study ( Table 2).…”
Section: Results Divided According To Time Of Onsetsupporting
confidence: 55%
“…Treatment of FN palsy following otologic surgery includes observation, corticosteroids, antiviral therapy, and surgical decompression [12]. Corticosteroids, compared to placebo, have been shown to significantly improve FN outcomes [32,33].…”
Section: Results Divided According To Time Of Onsetmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, Kronenberg et al [7] presented a suprameatal approach to avoid facial nerve injury. The ratio of facial paralysis following cochlear implantation has been reported as 0.07-1.1% in the literature, and most of these reported cases were delayed onset paralysis [8][9][10] . In our previous cochlear implantation case series, we did not observe early or immediate facial paralysis after cochlear implantation.…”
Section: Discussionmentioning
confidence: 99%